AIDS and the ancestor cult: Toward a contextual theological conversation in the "New" South Africa. - Knox, Peter. (University of Ottawa (Canada), 2005)
This thesis investigates the meanings of Christian salvation within the context of the AIDS pandemic in South Africa. The pandemic poses enormous social, economic, developmental, as well as theological, problems for the fledgling democracy of South Africa. The pandemic has stricken the whole continent of Africa particularly forcefully, but in South Africa, where there had been expectations of a new order since the peaceful overthrow of the apartheid government in 1994, the expectations of "salvation" for the nation have been cruelly dashed by the force of the pandemic. With the aid of a lemma, I show that salvation is neither equivalent to and coextensive with political liberation, nor reducible to a unassignable spiritual state of being in relationship with Christ. Rather, as in Old Testament writings, salvation should be understood as having direct bearing on the immediate context of the person or nation in question---which understanding is frequently overlooked. In the context of AIDS, then, an understanding of salvation should have a bearing on social death due to the stigma of the condition; on the healing of the illness itself; on the reconciliation of people whose lives are immediately affected by the pandemic; on addressing those social factors which allow the spread of HIV, and on the tardiness in the provision of effective medical care for people with various AIDS-related illnesses. In the thesis I demonstrate that another unavoidable dimension of the "New" South Africa is the traditional Bantu cult of the ancestors. I cite numerous reports showing that the cult is widely practiced, even by Christians. The ancestors are therefore an unavoidable dimension of the common religious understanding of life. If the meanings of salvation in the pandemic are being sought, then it would be a grave oversight not to consider how they relate to the cult of the ancestors. This research has shown that the cult of the ancestors makes a definite contribution to an understanding of salvation in the context of the pandemic in South Africa. (Abstract shortened by UMI.)
Keywords: Anthropology, Cultural.; Theology.